RECONSTRUCTION CONSUMER PROTECTION IN PROPERTY DEVELOPER INSOLVENCY: A COMPARATIVE LEGAL CRITIQUE OF INDONESIA, SINGAPORE, AND AUSTRALIA - Maulana, Fadli (NOMOI Law Review, 2025)
Consumer protection in failed property development transactions involving bankrupt developers remains a structural weakness within Indonesia’s legal system. Consumers often face legal and financial burdens, such as ongoing loan obligations, despite project non-performance and lack of priority in bankruptcy proceedings. This study aims to analyze Indonesia’s consumer protection framework in this context using normative-juridical and comparative legal methods, examining best practices from Singapore and Australia. The research finds that Indonesia lacks an integrated regime across contract, consumer, and insolvency law, resulting in fragmented protections and systemic risk to consumers. By contrast, Singapore mandates escrow accounts and standardized sale contracts, while Australia imposes statutory trust accounts, home warranty insurance, and enforceable certification and inspection schemes. Furthermore, both jurisdictions provide institutional redress mechanisms, including tribunals with binding adjudicative authority. The study also highlights actual cases, including the Porter Davis insolvency response and QCAT decisions, that demonstrate the efficacy of coordinated regulatory and adjudicative frameworks. The findings suggest that Indonesia must adopt structural legal reforms, including escrow mandates, recognition of consumers as preferential creditors, and enhanced supervisory institutions. This research is useful for legislators, regulators, and scholars seeking to construct a more equitable, accountable, and resilient consumer protection system in Indonesia’s property sector.